An underground view of surface hydrology: what can piezometers tell us about river floods and droughts? - Pelletier, Antoine; Andréassian, Vazken (Comptes Rendus. Géoscience)
The role of aquifers in extreme hydrological events has been highlighted in numerous different contexts, both for river high flows and low flows. Many aquifers are monitored by networks of piezometers that measure groundwater levels: their long-term records allow for a joint analysis of contemporaneous streamflow time series. Yet, groundwater level data are rarely used in surface hydrological modelling approaches, because of the huge complexity of river–aquifer interactions. We propose a simple correlation analysis between yearly extrema of groundwater level and streamflow time series, performed on a large set of 107 catchments and 355 piezometers, located throughout mainland France. We show that it is possible to discriminate between aquifers that correlate only with high-flow events, only with low flows, with both types of events or with none of them. Our typology presents new opportunities to characterise the surface–groundwater exchanges, which can be very important for understanding the occurrence of river extremes.